Preserved dopaminergic homeostasis and dopamine‐related behaviour in hemizygous TH‐Cre mice. (22nd August 2016) - Runegaard, Annika H.; Jensen, Kathrine L.; Fitzpatrick, Ciarán M.; Dencker, Ditte; Weikop, Pia; Gether, Ulrik; Rickhag, Mattias
Abstract: Cre‐driver mouse lines have been extensively used as genetic tools to target and manipulate genetically defined neuronal populations by expression of Cre recombinase under selected gene promoters. This approach has greatly advanced neuroscience but interpretations are hampered by the fact that most Cre‐driver lines have not been thoroughly characterized. Thus, a phenotypic characterization is of major importance to reveal potential aberrant phenotypes prior to implementation and usage to selectively inactivate or induce transgene expression. Here, we present a biochemical and behavioural assessment of the dopaminergic system in hemizygous tyrosine hydroxylase (TH)‐Cre mice in comparison to wild‐type (WT) controls. Our data show that TH‐Cre mice display preserved dopaminergic homeostasis with unaltered levels of TH and dopamine as well as unaffected dopamine turnover in striatum. TH‐Cre mice also show preserved dopamine transporter expression and function supporting sustained dopaminergic transmission. In addition, TH‐Cre mice demonstrate normal responses in basic behavioural paradigms related to dopaminergic signalling including locomotor activity, reward preference and anxiolytic behaviour. Our results suggest that TH‐Cre mice represent a valid tool to study the dopamine system, though careful characterization must always be performed to prevent false interpretations following Cre‐dependent transgene expression and manipulation of selected neuronal pathways. Abstract : Phenotypic characterization of the TH‐Cre mouse strain validates its use to target and study the dopamine system. Hemizygous TH‐Cre mice display preserved dopaminergic homeostasis with unaltered levels of TH and dopamine as well as unaffected dopamine turnover in striatum. TH‐Cre mice demonstrate normal responses in basic behavioural paradigms related to dopaminergic signalling (Sagittal and coronal brain sections in illustration were modified from Paxinos and Franklin, 2001).